In‐Situ Annealing of the (110) and (001) Surfaces of SrTiO3 Nanocuboids by High‐Resolution Transmission Electron Microscopy. Issue 19 (6th August 2018) - Liberti, Emanuela; Kirkland, Angus I.
Abstract : Thermal annealing of SrTiO3 substrates is used in a wide range of applications, including films and nanoparticle growth, electronic devices, catalysis, and photocatalysis. To predict and control reaction kinetics during high temperature treatments, it is essential to understand dynamics in real time. For this purpose, in‐situ electron microscopy techniques are increasingly used, as structural changes can be monitored at the nanoscale. Herein, the authors report on the surface evolution of the (110) and (001) surfaces of SrTiO3 nanocuboids observed in‐situ during thermal treatment at 800 °C, using aberration corrected high‐resolution transmission electron microscopy. By establishing a threshold for the cumulative electron dose, below which only temperature induced growth occurs, the authors observe the formation of epitaxial, faceted TiO islands, in agreement with previously reported results on the thermal treatment of (001) surfaces of SrTiO3 in reducing environments. When surface evolution is a consequence of the combined effects of electron beam damage and temperature‐induced growth, structural modification of the cuboids is highly dynamic. In this case formation of faceted islands occurs rapidly in conjunction with sublimation of the cuboids at considerably larger speeds than in the case of thermal treatment. Abstract : This work investigates thermal annealing of SrTiO3 nanocuboids by in‐situ aberration corrected high‐resolution transmission electron microscopy (HRTEM). Below a fixed cumulative electron dose, in a temperature‐induced growth regime, the authors observe the formation of epitaxial, well‐faceted TiO islands. The combined effect of electron beam damage and temperature‐induced growth induces highly dynamical structural modification of the cuboids, including the formation of nanoparticles.